PELAKSANAAN PEMBELAJARAN MATEMATIKA DALAM KURIKULUM MERDEKA MANDIRI BERUBAH DI SDN 2 LIMBOTO - Hasan, Citra; Anwar, Herson; Nadjamuddin, Asriyati (LP2M IAIN Sultan Amai Gorontalo, 2024)
This research aims to describe how implementation of mathematics learning in the independent curriculum has changed. The method used in this research is a qualitative phenomenological approach with data collection through observation, interviews and documentation. The results of this research show that at the planning stage of mathematics learning in the Independent Change Curriculum, it has been implemented well and structured, including teachers analyzing learning outcomes, formulating learning objectives, creating a flow of learning, and creating teaching modules that contain components in accordance with the modules in the curriculum Independent. The implementation of mathematics learning in the independent and changing curriculum has gone quite well, and in the learning, the teacher prepares the class to be comfortable and conducive. Students are actively involved in the learning process, teacher master the learning material well, but in terms of the use of learning media, it needs to be varied and adapted to the characteristics of the students. The evaluation of mathematics learning in the independent curriculum changed to using three assessments, namely diagnostic assessment, formative assessment and summative assessment. Keywords: Implementation of Learning; Mathematics Learning; Independent Curriculum Changes